2021
DOI: 10.23939/chcht15.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of DENOx SCR over Cu-, Fe- and Mn-FAU Catalysts

Abstract: Ab initio calculations based on the density functional theory were used. A cluster model of the faujasite zeolite structure (Al2Si22O66H36) with metal particles adsorbed above the aluminium centres was used. The NO and NH3 adsorption processes, individual and co-adsorption, have been studied over metal nanoparticles bound into zeolite clusters. Several configurations, electronic structure (charges, bond orders) and vibration frequencies have been analyzed to determine feasible pathways for the deNOx reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…As part of the publication, calculations using the DFT method were also performed. For this purpose, a cluster model of zeolites was developed and computational processes for adsorption were performed [21][22][23].…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…As part of the publication, calculations using the DFT method were also performed. For this purpose, a cluster model of zeolites was developed and computational processes for adsorption were performed [21][22][23].…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…As mentioned earlier, a precise understanding of the reaction mechanism is required to fully explore the SCR process and optimise the conditions of the process [16]. Theoretical calculations allow different variants to be tested in a relatively quick and reasonably lowcost way, allowing a wider view of the entire catalytic system, as well as the investigation of, for example, important intermediates that decompose rapidly and are consequently more difficult to analyse in experimental studies [37]. Theoretical studies have also shown that systems in which metal deposition occurs in the form of an oxygen-bridged dimer between metal atoms (M 1 -O b -M 2 ) are especially important in the deNOx process [38].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for more efficient catalysts for the deNOx process, it is also extremely important to understand the mechanism of intermediate reactions that result in the production of harmless nitrogen and water molecules [ 36 , 37 ]. In this aspect, theoretical studies prove to be indispensable, because they allow for a more comprehensive view of the catalytic system and make it possible to test many variants in a relatively short time [ 38 ]. The studies have shown that the systems representing metallic dimers with an oxygen atom in the bridge position (M–O–M) have proven to be particularly important [ 39 ].…”
Section: Introductionmentioning
confidence: 99%